Common insect pests in homes and cultural heritage sites - Bouthaina Hasnaoui; Fabien Fohrer; Philippe Parola; Jean-Michel Berenger (PeerJ)
Insect pests represent a threat to the integrity of historic buildings and homes, causing serious losses and irreversible damage. These pests can cause extensive damage to organic materials, including wood, textiles, and paper. Beetles, termites, booklice, moths, and cockroaches are just some of the main insect pests that are frequently found in historic buildings and homes. Beetle species such as the furniture beetle and the powderpost beetle are well recognised for their capacity to infest and feed on wood. Termite infestations can remain undetected and cause considerable damage that may even lead to the complete destruction of a building’s structural integrity. Cloth moth larvae are known to damage textiles, including carpets, furniture, clothes, and tapestries. Some wood-destroying species of cockroaches have the potential to harm historic buildings. Booklice have the ability to eat cellulose fibres found in archived articles and artefacts stored in heritage buildings, causing deterioration and damage to documents over time. This article reviews the literature and presents an overview of the major insect pests belonging to five known orders Coleoptera, Blattodea, Lepidoptera, Zygentoma (long-tailed silverfish) and Psocoptera, which pose a threat to households, museums, depositories, libraries, and cultural heritage buildings. We also discuss their biology, their impact on human health, and the various potential approaches to identifying them.